APLIKASI KONSEP KONSERVASI PADA KAWASAN BANTARAN SUNGAI STUDI KASUS: CLARKE QUAY - Ari Widyati Purwantiasning (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2010)
ABSTRACTAs a result of excursion studies’ series in Singapore in October 2009, severalstudies on the region in Singapore had been summarized successfully, including theassessment of conservation areas.Singapore River as one of river bank conservationarea, known as Clarke Quay, has been touched on during this excurcion studies.. Thispaper will examine how the concept of conservation had been applied to to this areaconsidering to promote a Clarke Quay tourist centre area. It also will study more abouthow the relationship of physical elements of the city with the concept of conservationnowadays.Keywords: conservation, Clarke Quay